Shanzhai pictorial anti-essentialism: Varejão’s depictions of Brazilian indigenous people - Balán, Laura (Frontiers in Communication, 2025)
Drawing on Critical Visual Discourse Analysis to examine how images reflect, produce, and challenge power relations, this paper analyzes how Adriana Varejão’s Invitation Figures I and II negotiate with historical scopic regimes and visual rhetorics of Otherness, identifying mechanisms of interpellation and viewer inclusion. I argue that Varejão’s strategy of appropriating 16th-, 17th-, and 18th-century artworks depicting Brazilian Indigenous peoples can be understood through the concept of shanzhai, as developed by Byung-Chul Han. Rather than imitating, shanzhai creations intervene in, parody, and transform original works, becoming more original than the original by addressing present concerns. This perspective contrasts with readings of her work as merely anthropophagic or simulacral. Understanding these artworks as shanzhai interventions enables an anti-essentialist reading of indigeneity in Brazil—one that challenges the racial and civilizational narratives historically used to naturalize subaltern social roles. I propose that Varejão’s images reveal how memory and imagination about the other and the self emerge as sedimented traces—constantly updated, cut, forgotten, and reassembled through the lens of the present. In this reconstruction of history, forgeries, copies, and shanzhai artifacts can carry as much epistemic weight as official documents, subverting dominant narratives and proposing alternative ways of seeing and knowing.